Where does the time go? Displacement of device-measured sedentary time in effective sedentary behaviour interventions: systematic review and meta-analysis - Segura-Jiménez, Víctor; Biddle, Stuart JH; De Cocker, Katrien; Khan, Shahjahan; Gavilán-Carrera, Blanca (Springer, 2022)
Objective: Our objective was to synthesize the evidence from interventions that have reduced sedentary behaviour and test the displacement of sedentary time into physical activity (light physical activity [LPA], moderate-to-vigorous physical activity [MVPA], standing, and stepping). Methods: Two independent researchers performed a systematic search of the EBSCOhost, PubMed, Scopus, and Web of Science electronic databases. Meta-analyses were performed to examine the time reallocated from sedentary behaviour to physical activity during working time and the whole day in intervention trials (randomized/non-randomized controlled/non-controlled). Results: A total of 36 studies met all the eligibility criteria and were included in the systematic review, with 26 studies included in the meta-analysis. Interventions showed a significant overall increase in worksite LPA (effect size [ES] 0.24; 95% confidence interval [CI] 0.05 to 0.43; P < 0.013) and daily LPA (ES 0.62; 95% CI 0.34 to 0.91; P = 0.001). A statistically significant increase in daily MVPA was observed (ES 0.47; 95% CI 0.26 to 0.67; P < 0.001). There was a significant overall increase in worksite standing time (ES 0.76; 95% CI 0.56 to 0.95; P < 0.001), daily standing time (ES 0.52; 95% CI 0.38 to 0.65; P < 0.001), and worksite stepping time (ES 0.12; 95% CI 0.04 to 0.20; P = 0.002). Conclusions: Effective interventions aimed at reducing sedentary behaviour result in a consistent displacement of sedentary time to LPA and standing time, both at worksites and across the whole day, whereas changes in stepping time or MVPA are dependent on the intervention setting. Strategies to reduce sedentary behaviour should not be limited to worksite settings, and further efforts may be required to promote daily MVPA
Keywords: Sedentarismo; Tiempo sedentario; Actividad física; Acelerometría